Perlindungan Hukum Hak Atas Tanah Adat Akibat Pemekaran Wilayah (Studi Penelitian Di Provinsi Gorontalo Khususnya Kabupaten Bone Bolango) - Suleman, Moh. Nikswanto S.; Thalib, Mutia Cherawaty; Mandjo, Julius T. (CV. ITTC INDONESIA, 2023)
This study raises issues related to legal protection for indigenous peoples who are affected by inaccurate boundaries due to regional expansion that occurred in Bone Bolango Regency. This study aims to determine the position of customary land rights due to regional expansion, and to determine the legal protection that will be obtained by indigenous peoples who are the result of regional expansion. The results obtained by the researchers are that the legal position of land rights that occurs as regional pemekawan has been regulated in Law Number 32 of 2004 regarding amendments to Law Number 22 of 1999 concerning Regional Government, and protection for indigenous peoples who feel disadvantaged because of the placement Unclear territorial boundaries from the government caused by regional expansion is to clearly define and mark boundaries at each regional boundary point for each region.